Ubiquitin specific peptidase 5 mediates Histidine‐rich protein Hpn induced cell apoptosis in hepatocellular carcinoma through P14‐P53 signaling. Issue 12 (20th June 2017) - Liu, Yi; Wang, Wei‐mao; Zou, Li‐yi; Li, Li; Feng, Lu; Pan, Ming‐zhu; Lv, Min‐yi; Cao, Ying; Wang, Hua; Kung, Hsiang‐fu; Pang, Jian‐xin; Fu, Wei‐ming; et al.
Abstract : Hpn is a small histidine‐rich cytoplasmic protein from Helicobacter pylori and has been recognized as a high‐risk factor for several cancers including gastric cancer, colorectal cancer, and MALT lymphoma. However, the relationship between Hpn and cancers remains elusive. In this study, we discovered that Hpn protein effectively suppressed cell growth and induced apoptosis in hepatocellular carcinoma (HCC). A two‐dimensional gel electrophoresis and mass spectrometry‐based comparative proteomics was performed to find the molecular targets of Hpn in HCC cells. It was identified that twelve proteins were differentially expressed, with USP5 being one of the most significantly downregulated protein. The P14 ARF ‐P53 signaling was activated by USP5 knockdown in HCC cells. Furthermore, USP5 overexpression significantly rescued the suppressive effect of Hpn on the viability of HCC cells. In conclusion, our study suggests that Hpn plays apoptosis‐inducing roles through suppressing USP5 expression and activating the P14 ARF ‐P53 signaling. Therefore, Hpn may be a potential candidate for developing novel anti‐HCC drugs.